2005
DOI: 10.1002/ajh.20419
|View full text |Cite
|
Sign up to set email alerts
|

Association between adverse pregnancy outcomes and maternal factor V G1691A (Leiden) and prothrombin G20210A genotypes in women with a history of recurrent idiopathic miscarriages

Abstract: Thrombophilia was implicated in the development of pregnancy complications, including recurrent idiopathic pregnancy loss, and is aggravated in women who are carriers of factor V G1691A (FV Leiden) and prothrombin (PRT) G20210A single-nucleotide polymorphisms (SNPs). Previous studies examined the role of FV-Leiden and PRT G20210A in recurrent pregnancy loss with conflicting results. Here we examined the prevalence of FV Leiden and PRT G20210A SNPs, in 200 women with 3 or more consecutive early (n = 87), late (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 59 publications
(69 reference statements)
1
22
1
1
Order By: Relevance
“…53,55,56,59,60,67,74,84,94,107 All but three of the 45 remaining studies satisfied HardyWeinberg criteria (χ2; test; P ≥ 0.05); these three were excluded. 77,103,108 Of interest, two of these studies 77,108 were in a small subset of studies conducted in non European white populations. Using a random effects model, the summary OR for 42 studies was 2.34 (95% CI: 1.88-2.92; P < 0.001), with moderate heterogeneity (I 2 = 45%; P < 0.001).…”
Section: Case-control Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…53,55,56,59,60,67,74,84,94,107 All but three of the 45 remaining studies satisfied HardyWeinberg criteria (χ2; test; P ≥ 0.05); these three were excluded. 77,103,108 Of interest, two of these studies 77,108 were in a small subset of studies conducted in non European white populations. Using a random effects model, the summary OR for 42 studies was 2.34 (95% CI: 1.88-2.92; P < 0.001), with moderate heterogeneity (I 2 = 45%; P < 0.001).…”
Section: Case-control Studiesmentioning
confidence: 99%
“…The OR in the first group was higher (ORs of 3.94 and 2.02, respectively; P = 0.11). Had the two Tunisian studies 77,108 been included, the difference would have been statistically significant (ORs of 4.35 and 2.02, respectively; P = 0.005). Differences may have resulted from relatively high (15% 62 and 11% 71 ) or low (1%…”
Section: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be as common as lower extremity deep venous thrombosis [7] or rare recurrent central retinal vein thromboembolic showering [8]. Some authors recommend testing for FVL mutation in women experiencing recurrent unexplained miscarriages [9]. Our patient had two risk factors stacked against him: first being a heterozygous FVL R506Q mutation carrier, and second enduring a protracted hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that adverse outcome or fatal course of pregnancy (recurrent miscarriages, intrauterine growth restriction, placenta abruption, still birth, and susceptibility to develop preeclampsia/ eclampsia) could be significantly connected with presence of thrombotic polymorphic genetic variants which act as single risk factor or, most probably, cooperate together [3][4][5][6][7]. Additionally, impact of thrombotic risk factors might be intensified by pathophysiological processes and circumferential factors [8][9][10].…”
Section: Introductionmentioning
confidence: 99%